A Meta-Analysis of Writing Interventions for Students With Learning Disabilities - Gillespie, Amy; Graham, Steve (Exceptional children, 2014)
In this meta-analysis, the impact of writing interventions on the quality of writing produced by students with learning disabilities (LD) was assessed. Ancestral and electronic searches were used to locate experimental, quasi-experimental, and within-subjects design studies with participants in Grades 1–12 with documented LD. The effects of writing interventions on participants’ writing quality were averaged across 43 eligible studies to calculate an average weighted mean effect size (ES). Average weighted mean ES were also calculated for six writing treatment subgroups that contained four or more studies each (i.e., strategy instruction, dictation, procedural facilitation, prewriting, goal setting, and process writing). Overall, writing interventions had a statistically significant positive impact on the writing quality of students with LD (ES = 0.74). All writing treatment subgroups also had positive average weighted ES, but only four were statistically different from zero (i.e., strategy instruction ES = 1.09, dictation ES = 0.55, goal setting ES = 0.57, and process writing ES = 0.43). In addition, treatments designed specifically to enhance writing processes (e.g., planning, revising) were only effective when instruction was provided. Implications for the types of writing treatments and the types of instruction that may be most beneficial to students with LD are discussed and directions for future research are provided.